Self-assembly of chemically modified graphene sheets in an external magnetic field. Issue 34 (21st June 2019) - Tong, Mingqiong; Cao, Jianda; Chen, Xiaoping; Zhang, Huanxia; Wu, Wen; Ma, Hui
Abstract : The rapid developments of effective self-assembly technologies indicated that ordered structures of GO could be produced using external field inducement. Abstract : The rapid developments of effective self-assembly technologies indicated that ordered structures could be produced using external field inducement. We designed the alignment of graphene oxide nanosheets grafted with the modified ferroferric oxide by the application of a magnetic field. The results indicated that the morphologies of graphene oxide went through some changes from disordered to semi-ordered in the final and, highly oriented wrinkled structures. The orientation mechanism of graphene oxide demonstrated that the geometric features of the wrinkles were related to the edge stresses and the elastic stiffness of the sheets, magnetic force of magnetic field to magnetic-particles. The prepared reduced graphene oxide fibers indicated that the sheets with magnetic precipitates underwent shrinkage in the radial direction when an external magnetic field was exerted and the interior sheets aligned along the direction of the magnetic field, which was supported by the proposed theories. It is expected that the research could contribute to the applications of flexible graphene-based materials in preparation and controlling the formation of wrinkles in single layer graphene.